Impact of marketing mix dimensions on the competitiveness of university centers - Tania Janette Marín-Orantes; María de la Cruz del Río-Rama; Dora Aguilasocho-Montoya; José Álvarez-García (Social Sciences and Humanities Open)
The aim of this research is to empirically contrast an explanatory model of how the elements of the marketing mix used in a university center (product, price, place, promotion, personnel, processes and physical evidence) influence its competitiveness from the point of view of its users (students). The methodology used for the analysis of the causal relationship proposed in the model is the Structural Equation Modeling (SEM) technique. The data were obtained from a structured survey applied to students of the Universidad Michoacana de San Nicolás de Hidalgo located in Michoacán, Mexico, obtaining a sample of 380 valid questionnaires. The results corroborate that the marketing mix strategy designed by higher education institutions has a direct and positive relationship with their competitiveness, as perceived by their students. It is verified that the marketing mix is a multidimensional construct made up of four dimensions, product/service, promotion, physical evidence/non-teaching service, price, and all of them have a similar importance in the configuration of the marketing mix.